Frederick Luis Aldama. Latino Comic Book Storytelling: An Odyssey by Interview. San Diego: ¡Hyperbole Books!, 2017. - Jessica Rutherford (Studies in 20th & 21st Century Literature, 2017)
Review of Frederick Aldama. Latino Comic Book Storytelling: An Odyssey by Interview. San Diego: ¡Hyperbole Books!, 2017.
Keywords: U.S. Latino comics; storytelling; alternative archives